(untitled) (International Journal of Engineering and Computer Science, 2017)
—A hypervisor is a piece of computer software, firmware or hardware that creates and runs multiple virtual machines. The hypervisor presents the guest operating systems with a virtual operating platform and manages the execution of the guest operating systems. Virtual switch which is a part of the hypervisor also called as hypervisor switch does the switching between VM traffic. Currently if two VMs those are interested in communication and if they are in same subnet then VM-VM traffic will traverse from source VM to destination VM through hypervisor switch. And if two VMs are in different subnet then traversing of packets will need external devices such as external switch and router which increases the traffic in the network. We can improve the quality of the system by implementing the functionality of router within the hypervisor.